Esterification of bio-oil from mallee (Eucalyptus loxophleba ssp. gratiae) leaves with a solid acid catalyst: Conversion of the cyclic ether and terpenoids into hydrocarbons - Hu, Xun; Gunawan, Richard; Mourant, Daniel; Wang, Yi; Lievens, Caroline; Chaiwat, Weerawut; Wu, L.; Li, Chun-Zhu (Elsevier BV, 2012)
Bio-oil from pyrolysis of mallee (Eucalyptus loxophleba ssp. gratiae) leaves differs from that obtained with wood by its content of cyclic ethers, terpenoids and N-containing organic compounds. Upgrading of the leaf bio-oil in methanol with a solid acid catalyst was investigated and it was found that the N-containing organics in the bio-oil lead to deactivation of the catalyst in the initial stage of exposure and have to be removed via employing high catalyst loading to allow the occurrence of other acid-catalysed reactions. Eucalyptol, the main cyclic ether in the bio-oil, could be converted into the aromatic hydrocarbon, p-cymene, through a series of intermediates including α-terpineol, terpinolene, and α-terpinene. Various steps such as ring-opening, dehydration, isomerisation, and aromatization were involved in the conversion of eucalyptol. The terpenoids in bio-oil could also be converted into aromatic hydrocarbons that can serve as starting materials for the synthesis of fine chemicals, via the similar processes.